Long non-coding RNA-small nucleolar RNA host gene 7 regulates inflammatory responses following spinal cord injury by regulating the microRNA-449a/TNF-α-induced protein 3-interacting protein 2 axis. Issue 4 (1st April 2022) - He, Chunlei; Xiao, Jianhua; Ye, Yongjun; Huang, Shiqiao; Zhong, Yanchun; Liu, Lulin; Liu, Wuyang; Liu, Sheng
ABSTRACT: The current study aimed to explore the anti-inflammatory effects of long non-coding RNA-small nucleolar RNA host gene 7 (lncRNA-SNHG7) and its mechanism in spinal cord injury (SCI) models. SCI models were established both in vivo and in vitro . Reverse transcription-quantitative PCR was performed to determine the expression levels of lncRNA-SNHG7 in SCI models. Bioinformatics analysis and dual-luciferase reporter assays were carried out to confirm the interaction between lncRNA-SNHG7 with microRNA (miR)-499a and TNF-α-induced protein 3-interacting protein 2 (TNIP2). In addition, cell viability, apoptosis, and the secretion of inflammatory cytokines were assessed by 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide (MTT) assay, flow cytometric analysis, and enzyme linked immunosorbent assay (ELISA), respectively. The results showed that lncRNA-SNHG7 was markedly downregulated in the SCI model group. LncRNA-SNHG7 directly bound to miR-499a, which in turn directly targeted TNIP2. In addition, TNIP2 was significantly decreased in SCI rats and lipopolysaccharide (LPS)-treated PC-12 cells. The in vitro results in PC-12 cells revealed that lncRNA-SNHG7 overexpression attenuated neuronal cell death and SCI-mediated inflammatory responses by regulating miR-449a expression. Furthermore, miR-499a knockdown inhibited LPS-induced PC-12 cell injury by targeting TNIP2. In conclusion, lncRNA-SNHG7 modulates the apoptosis and inflammation of PC-12 cells by regulating the miR-449a/TNIP2/NF-κB signaling pathway. Graphical Abstract: uf0001